2000
DOI: 10.1159/000045634
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a Highly Sensitive Urinary and Serum IL-6 Assay in Patients with Diabetic Nephropathy

Abstract: Background/Aim: Interleukin-6 (IL-6) promotes the growth of renal mesangial cells. IL-6 may play a major role in such mesangial proliferation, but there has been little research on IL-6 in relation to diabetic nephropathy because of the difficulty in measuring urinary and serum IL-6 levels. Using a newly developed, highly sensitive IL-6 assay, we studied the relationship between serum and urinary IL-6 and diabetic nephropathy. Methods: We investigated 72 patients with type 2 diabetes. Urinary and serum IL-6 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 14 publications
2
69
0
2
Order By: Relevance
“…18 There is also evidence that IL-6 production by human monocytes isolated from healthy volunteers is enhanced during 24-hour incubation in high-glucose medium. 19 Previous studies have demonstrated increased circulating levels of TNF-␣ and IL-6 in diabetic patients, 3,5-8 with a significant correlation of IL-6 levels with HbA 1 c, 7 progression of diabetic nephropathy, 8 and amelioration of glycemic control after treatment. 6 In a more general sense, an augmented acute-phase response may be a mechanism that explains many of the clinical and biochemical features of type 2 diabetes and its complications.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…18 There is also evidence that IL-6 production by human monocytes isolated from healthy volunteers is enhanced during 24-hour incubation in high-glucose medium. 19 Previous studies have demonstrated increased circulating levels of TNF-␣ and IL-6 in diabetic patients, 3,5-8 with a significant correlation of IL-6 levels with HbA 1 c, 7 progression of diabetic nephropathy, 8 and amelioration of glycemic control after treatment. 6 In a more general sense, an augmented acute-phase response may be a mechanism that explains many of the clinical and biochemical features of type 2 diabetes and its complications.…”
Section: Discussionmentioning
confidence: 98%
“…4 Moreover, several studies have demonstrated elevated levels of IL-6 and tumor necrosis factor-␣ (TNF-␣) among individuals both with features of the insulin resistance syndrome and with clinically overt type 2 diabetes mellitus. [5][6][7][8] The aim of the present study was to test whether circulating levels of cytokines are regulated by glucose levels in humans. The study protocol was designed to measure serum TNF-␣, IL-6 and interleukin-18 (IL-18) concentrations during acute hyperglycemia in subjects with normal or impaired glucose tolerance (IGT); a role for IL-18 in plaque destabilization has recently been suggested, 9 and stress hyperglycemia is an important risk factor for post-myocardial infarction mortality in subjects with or without diabetes.…”
mentioning
confidence: 99%
“…25 The intra-day and inter-day coefficients of variation (CV) of this assay were 1.5-5.5% and 3.3-4.5%, respectively. This assay format is based on the two-step sandwich CL-EIA method as follows: aliquots 50 µL of each sample were added to 250µ L of suspension of ferrite microparticles coated with a monoclonal antibody against IL-6 as a solid phase and There were no significant differences in IL-6 concentrations (period 1) between the smokers and non-smokers (p=0.48) or between patients with and without periodontal disease (p=0.37).…”
Section: Stimulated Saliva Sample Preparationmentioning
confidence: 88%
“…Expression studies have also shown IL-6 mRNA in the mesangium of renal specimens from diabetic subjects [10]. IL-6 has in fact been shown to be the main stimulus for the hepatic production of CRP, and its gene transcripts are expressed in human atheromatous lesions.…”
mentioning
confidence: 98%